Effect of the Implementation of Employee Training & Development Programme on Employee Performance : (Case study of PT. Federal International Finance (FIFGROUP) Batu City branch) - Abrori Indra Setiawan; Daris Zunaida; Ainul Chanafi (International Journal of Social Science and Community Service, 2024)
This study aims to understand and assess the impact of the Implementation of Employee Training & Development Programs on Employee Performance (Case Study of PT. Federal Internasional Finance (FIFGROUP) Batu City Branch), both individually and overall. The research method used is quantitative. The data collection technique applied is a questionnaire. The data analysis methods employed include the measurement of instruments, encompassing validity and reliability testing, classical assumption testing, which covers normality, linearity, multicollinearity, and heteroscedasticity tests, as well as hypothesis testing, which includes multiple linear regression analysis, t-test, F-test, and determination coefficient. The findings of the study indicate that both variables, namely the employee training & development programs, have an individual impact on employee performance (case study of PT. Federal Internasional Finance (FIFGROUP) Batu City Branch). Additionally, the employee training & development program variables also have an overall impact on employee performance (case study of PT. Federal Internasional Finance (FIFGROUP) Batu City Branch).